Percepções dos recursos ambientais (terra, água, plantas e animais) no Assentamento Santa Helena - São Carlos/SP - Cassimiro, Murilo Otávio (Universidade Federal de São Carlos, 2018)
Humans have always been related to the environmental resources, in the search to progress and to develop the place where they lived, also aiming to ensure a future to the descendants. This relation was transformed over the years, with industrial, agricultural and technological development, they became cooler. In the rural environment, the people who live and develop there tend to have a greater affectivity towards resources, the constant presence between them strengthens these relationships, thus, Agrarian settlements are places where there is a greater connection of beings and environment. Knowing how these people have built their relationships with resources and what the current environment means to them, is important when thinking about development policies for Settlement development, these particularities serve as an essential information to take in mind when discussing and seeking improvements, elucidating the subjective reflections direct at an approximation between public organs and settlements. Thus, the general objective of the research was to describe and analyze the relationships between the settlers of the Santa Helena Settlement, in São Carlos/SP, and the environmental resources earth, water, plants and animals. The research presents two methodological steps, the first one, a bibliographical survey on the essential subjects in the dissertation and the second one based on the qualitative research and the case study, developed with the settlers in the Santa Helena Settlement, through semi structured interviews. From this, the central relations of each resource present in the settlers' speeches were extracted and a part of Lévi-Strauss's theory of structuralism, the binary pairs, a conception of opposition and correlation was used as data analysis. The main points of this relationship. It was then concluded that the present work has been able to answer the questions and objectives described, as well as elucidate the importance of identity, environmental knowledge and subjective issues of each person, in addition to a critical approach to agrarian reform policies and Sustainable Development Projects. It is observed a valuation of the environmental resources by the settlers, besides the pride of a healthy production. Leaving thus, several questions and perspectives for future work that seek to encompass the perceptions of resources, these distinct communities and the dynamics of the work involved.
Keywords: Recursos Ambientais; Assentamento; Terra; Água; Plantas; Animais; Environmental resources; Settlement; Earth; Water; Plants; Animals; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::CONSTRUCOES RURAIS E AMBIENCIA::ASSENTAMENTO RURAL; OUTROS; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA RURAL